Development of SSR Markers in Hickory (Carya cathayensis Sarg.) and Their Transferability to Other Species of Carya - Li, Juan; Zeng, Yanru; Shen, Dengfeng; Xia, Guohua; Huang, Yinzhi; Huang, Youjun; Chang, Jun; Huang, Jianqin; Wang, Zhengjia (Current Genomics, 2014)
Hickory (Carya cathayensis Sarg.), an important nut-producing species in Southeastern China, has high economic value, but so far there has been no cultivar bred under species although it is mostly propagated by seeding and some elite individuals have been found. It has been found recently that this species has a certain rate of apomixis and poor knowledge of its genetic background has influenced development of a feasible breeding strategy. Here in this paper we first release SSR (Simple sequence repeat) markers developed in this species and their transferability to other three species of the same genus, Carya. A total of 311 pairs of SSR primers in hickory were developed based on sequenced cDNAs of a fruit development-associated cDNA library and RNA-seq data of developing female floral buds and could be used to distinguish hickory, C. hunanensis Cheng et R. H. Chang ex R. H. Chang et Lu, C. illinoensis K. Koch (pecan) and C. dabieshanensis M. C. Liu et Z. J. Li, but they were monomorphic in both hickory and C. hunanensis although multi-alleles have been identified in all the four species. There is a transferability rate of 63.02% observed between hickory and pecan and the markers can be applied to study genetic diversity of accessions in pecan. When used in C. dabieshanensis, it was revealed that C. dabieshanensis had the number of alleles per locus ranging from 2 to 4, observed heterozygosity from 0 to 0.6667 and expected heterozygosity from 0.333 to 0.8667, respectively, which supports the existence of C. dabieshanensis as a separate species different from hickory and indicates that there is potential for selection and breeding in this species.
Keywords: C. hunanensis